The Effectiveness and Contribution of Hotel and Restaurant Tax Revenue to PAD Palopo City - Ekki Satria Jaya; Eko Edy Susanto (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Regional Original Income is revenue from local tax levies, regional levies, separated regional wealth management and other income. Restaurant tax and hotel tax are included in local taxes. Restaurants and hotels are potential sectors in increasing the effectiveness of tax revenues and their contributions can spur economic development in Palopo City. The purpose of this study was to determine the effectiveness and contribution of restaurant taxes and hotel taxes to PAD in Palopo City. The research was conducted at the Regional Revenue Service of Palopo City. Design/methodology/approach: The analytical method used is a descriptive method, namely analyzing the realization of restaurant tax and hotel tax realization data from 2016-2020. Findings: The results of the overall study The effectiveness of restaurant tax revenues and hotel taxes in 2016-2020 is very effective. Revenue from restaurant tax and hotel tax in 2016-2020 made a good contribution to PAD. Practical implications: The leadership of DISPENDA should be committed to the targets to be achieved every year, and strive to increase the contribution of restaurant taxes and hotel taxes to local revenues. Originality/value: The paper is original Paper type: Research paper